2006
DOI: 10.1021/jf060682v
|View full text |Cite
|
Sign up to set email alerts
|

Positional Distribution of Conjugated Linoleic Acid in Triacylglycerol of Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae was cultivated in the presence of cis-9,trans-11 or trans-10,cis-12 isomers of free conjugated linoleic acid (CLA), and the effects of the isomers on the regioisomerisms of triacylglycerol (TAG) of the yeast were elucidated. Both isomers constituted about 34% of all fatty acids and increased drastically the number of different TAG species. Nearly all of the species contained CLA in at least one sn-position. In the most abundant species analyzed (20% of total species), the cis-9,trans-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Previous studies have shown that the TAG content of the yeast cells cultivated in the presence of t 10 ,c 12 CLA isomer was remarkably lower compared to the control cells, whereas the c 9, t 11 isomer raised the TAG content (Jaakola et al . , ). Such results could be caused by two scenarios, firstly by affecting TAG biosynthesis and secondly by affecting TAG degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the TAG content of the yeast cells cultivated in the presence of t 10 ,c 12 CLA isomer was remarkably lower compared to the control cells, whereas the c 9, t 11 isomer raised the TAG content (Jaakola et al . , ). Such results could be caused by two scenarios, firstly by affecting TAG biosynthesis and secondly by affecting TAG degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The fat reducing effect of t 10 ,c 12 CLA has been found and characterized also in Saccharomyces cerevisiae (Jaakola et al . , ). A conspicuous similarity between mammalian and yeast cells has been observed, as in the yeast t 10 ,c 12 CLA also caused a dramatic decrease in the triacylglycerol (TAG) content and reduced desaturation of fatty acids (FA).…”
Section: Introductionmentioning
confidence: 99%
“…8,9) Differences in FAs as substrates of TG biosynthesis in PSPA cells altered the composition of the TG molecular species. Especially, cultured at 6 d, the addition of each LCFA to the cells increased TG molecular species containing added FAs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Individual TG molecular species of body fat are not equally synthesized, and some molecular species are preferentially synthesized. [6][7][8][9] Previous reports have shown that the positional distribution of FAs among the three positions in TG molecular species was due to a non-random process. 10,11) Moreover, C16:0 and C18:1 were usually the main FA in body fat TGs though diets with different FA compositions were fed to the pigs.…”
mentioning
confidence: 99%
“…containing polyunsaturated FAs, GC is less suitable than nonaqueous (NA) RP‐HPLC. Some papers describing TAGs from yeast identified only the sum of carbon atoms and the sum of double bonds in all three acyl chains, while others succeeded in determining the structure of individual acyls.…”
Section: Introductionmentioning
confidence: 99%